2014
DOI: 10.4049/jimmunol.1302616
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Chemokine, Cytokine, and Growth Factor Serum Levels in BRAF-Mutant Melanoma Patients during BRAF Inhibitor Treatment

Abstract: The purpose of this study is to profile the changes in the serum levels of a range of chemokines, cytokines, and growth and angiogenic factors in MAPK inhibitor–treated metastatic melanoma patients and to correlate these changes with clinical outcome and changes in melanoma tissue biopsies taken from the same patients. Forty-two chemokine, cytokine, angiogenic, and growth factors were measured in the sera of 20 BRAF inhibitor–treated and four combination BRAF and MEK inhibitor–treated metastatic melanoma patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 53 publications
4
45
0
3
Order By: Relevance
“…Again supporting these RNA expression findings are the RPPA data showing on-treatment LCK antibody levels (an immune marker) to be among the most highly correlated with RECIST responses ( Figure 6I). Taken together, these observations suggest that tumors with primed immune systems might be better poised for response to treatment, consistent with a recent report on prognostic immune serum markers in a BRAF inhibitor trial (35) and with the observation that microarray-based immune infiltration signatures positively correlate with survival in non-BRAFi-treated melanoma patient populations (36)(37)(38)(39). Additionally, the large-scale TCGA (The Cancer Genome Atlas) study has confirmed that elevated lymphocytic RNA-seq signatures and LCK RPPA signals positively correlate with outcome in over 300 patients (https://tcga-data.…”
Section: Discussionsupporting
confidence: 74%
“…Again supporting these RNA expression findings are the RPPA data showing on-treatment LCK antibody levels (an immune marker) to be among the most highly correlated with RECIST responses ( Figure 6I). Taken together, these observations suggest that tumors with primed immune systems might be better poised for response to treatment, consistent with a recent report on prognostic immune serum markers in a BRAF inhibitor trial (35) and with the observation that microarray-based immune infiltration signatures positively correlate with survival in non-BRAFi-treated melanoma patient populations (36)(37)(38)(39). Additionally, the large-scale TCGA (The Cancer Genome Atlas) study has confirmed that elevated lymphocytic RNA-seq signatures and LCK RPPA signals positively correlate with outcome in over 300 patients (https://tcga-data.…”
Section: Discussionsupporting
confidence: 74%
“…HLA-class I molecules are often downregulated or lost in tumor cells and play a key role in immune escape (30)(31)(32). A study by Carreteto and colleagues (33) showed that higher HLA class I gene expression was observed in regressing but not in progressing metastases from microdissected tumor regions, supporting the idea that the nature of HLA class I alterations in tumor cells may contribute to antitumor effects of therapeutic interventions. Our observation of MAPK inhibition induced apoptosis, increase of MHC class I and/or II along with the decrease of immunosuppression factors in most of the human tumor cell lines, and in CT26 tumors when combined with anti-PD-1 antibody in vivo is intriguing.…”
Section: Discussionmentioning
confidence: 76%
“…Evaluating HLA-I expression in melanoma biopsies would help define eligibility of patients for TNF blockade treatment. In addition, emerging therapies for the treatment of melanomas, such as anti-CTLA4 (50), and BRAF V600E inhibitors (7,8), are associated with CD8 þ T-cell immune response and TNF production, even in patients with disease progression. Macrophage-derived TNF is important for BRAF V600E melanoma growth in vivo and confers resistance to MAPK pathway inhibitors (16).…”
Section: Discussionmentioning
confidence: 99%
“…Injection of high levels of recombinant TNF triggers necrosis of melanoma, not only in mice, but also in humans and is currently used in isolated limb perfusion in the clinic (2). In sharp contrast, it has been recently shown that TNF, which is produced in patients treated with BRAF V600E inhibitors (7,8), may confer treatment resistance of human melanoma by increasing Twist1 levels (9). The role of TNF in melanoma has been further investigated in mice using B16 melanoma cells, which do not express TNF endogenously (10).…”
Section: Introductionmentioning
confidence: 99%